Case report and operative management of obstructed epigastric hernia containing gall bladder: a rare entity - Thurwal, Kartik; Kumari, Seema (International Surgery Journal, 2020)
An obstructed epigastric hernia containing gall bladder is a very rare entity and there are only few cases described in literature previously. A 69 year old woman presented at the emergency department at 1.00 a.m. with complains of pain and swelling in upper abdomen and having recurrent vomiting. As patient was sick and there was no imaging facility available at that time, patient was taken to OT in view of obstructed epigastric hernia. When abdomen was opened hernia sac containing gall bladder was seen. Then cholecystectomy and repair of the abdominal wall defect were performed. The patient recovered very well and was discharged on day 7.